The taxonomic and phylogenetic status of digeneans from the genus Timoniella (Digenea: Cryptogonimidae) in the Black and Baltic seas - Kvach, Y; Bryjová, A; Sasal, P; Winkler, H M (Journal of helminthology, 2018)
Timoniella spp. are cryptogonimid flukes (Digenea: Cryptogonimidae) that parasitize the guts of fish in brackish waters. Timoniella imbutiforme, a species from the Mediterranean Sea, is recorded in the Black Sea, while T. balthica has been described from the Baltic Sea. In this paper, we clarify the taxonomic status of Timoniella populations in the Baltic and Black seas. Adults and metacercariae of Timoniella spp. were sampled from localities in the Mediterranean Sea (France), Black Sea (Ukraine) and Baltic Sea (Germany) and subjected to molecular and morphological analysis, including Bayesian phylogenetic reconstruction based on concatenated sequences of ITS1-ITS2-28S. This allowed us to construct a new key to species of the genus Timoniella. Our results suggest that T. balthica forms part of the Boreal-Atlantic relict fauna of the Black Sea and should now be considered a junior synonym of T. imbutiforme.
Keywords: shluková analýza; fylogeneze; zvířata; RNA ribozomální 28S; Oceans and Seas; nemoci ryb; infekce červy třídy Trematoda; Cluster Analysis; Fish Diseases; mezerníky ribozomální DNA; Trematoda; Trematode Infections; Sequence Analysis, DNA; DNA helmintů; Phylogeny; sekvenční analýza DNA; DNA, Ribosomal Spacer; mikroskopie; Animals; Microscopy; DNA, Helminth; RNA, Ribosomal, 28S; oceány a moře